Managing talent : a short guide for the digital age - Rugg-Gunn, Mike (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"Recruiting, selecting, retaining, and developing great people is essential for any successful business. And the combination of digital transformation and post-pandemic work realities presents major challenges for all organisations. This book provides best practice talent management guidance for businesses undertaking digital transformation or facing digital disruption. Taking the reader through the stages of talent acquisition, selection, retention and development, this practical and concise book: sets out, assesses and predicts how the digital revolution impacts talent management practices, and helps the reader navigate the journey from an analogue to a digital organisation; updates talent management concepts, and illustrates these with examples and cases of best practice across the business world; and enables senior leaders, talent management professionals and managers to quickly access and implement key learnings through the use of practitioner point summaries and a set of Ten Top Tips in each chapter. The book provides practical insights, grounded in research, into how to manage talent in a fluid and dynamic world of digital change and is aimed at senior leaders and managers, and the HR community. It clearly shows how organisations undertaking a digital journey need to flex and adapt their talent management processes"--
Introduction -- The Business Context -- Recruitment -- Selection -- Retention -- Development -- Conclusions: So what? And where do we go from here?
Keywords: Personnel management; Digital media; Ability; BUSINESS & ECONOMICS / Human Resources & Personnel Management; BUSINESS & ECONOMICS / Careers / General; BUSINESS & ECONOMICS / Careers / Job Hunting